Effects of the number of days and the filling sequence of animal skin-bags used for the traditional production of Algerian Bouhezza raw goat cheese on physicochemical composition, α-tocopherol, cholesterol content and stability. (August 2021) - Senoussi, Asma; Schadt, Iris; Saoudi, Zineddine; Zitoun Hamama, Ouarda Aissaoui; Zidoune, Mohammed Nasereddine; Carpino, Stefania; Marino, Vita Maria
Abstract: Traditional Algerian Bouhezza cheese is produced inside animal skin-bags with a fermented, buttermilk-like product, Lben. Two Bouhezza cheeses were simultaneously made in two skin-bags in each of two sequential years. Bags had a defined filling sequence (first or second) with Lben for the same batch. Samples from each bag were collected at days 7, 30 and 60 to obtain 6 samples per year and a total of 12 samples. The effects of number of days and filling sequence on gross composition, α-tocopherol, cholesterol content and stability were evaluated. With more days, dry matter, protein, fat, cholesterol and α -tocopherol contents increased and pH decreased ( P < 0.01). At 60 d 100 g of Bouhezza contained 39.2 ± 7.04 mg of cholesterol. Cholesterol was never protected and oxidation was evident. Oxidation was highest in cheeses from the second-filled bags during the first 30 d of production ( P < 0.05).